2018
DOI: 10.18632/oncotarget.24711
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicle-encapsulated miR-30e suppresses cholangiocarcinoma cell invasion and migration via inhibiting epithelial-mesenchymal transition

Abstract: Early-staged cholangiocarcinoma (CCA) is difficult to diagnose due to its high potential for invasion and metastasis. Epithelial-mesenchymal transition (EMT) is induced by transforming growth factor-β (TGF-β) in a process thought to be important for invasion and metastasis in several cancers, including CCA. Although microRNAs (miRNAs) have been implicated in the pathogenesis of several malignancies, their roles to CCA are not clearly understood. Some miRNAs were reported to be included in extracellular vesicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 37 publications
0
40
0
Order By: Relevance
“…This mechanism of EV-mediated intercellular communication has been revealed by several authors (13,(15)(16)(17). We previously reported that miR-30e could be transferred by cholangiocarcinoma (CCA) cell-derived EVs, and suppress recipient CCA cell invasion and migration (18). In PDAC, some investigators reported that EVencapsulated miRNAs, such as miR-196a, miR-1246, or miR-4644, could contribute to tumor development and play crucial roles in the diagnosis as tools of liquid biopsy (19)(20)(21).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…This mechanism of EV-mediated intercellular communication has been revealed by several authors (13,(15)(16)(17). We previously reported that miR-30e could be transferred by cholangiocarcinoma (CCA) cell-derived EVs, and suppress recipient CCA cell invasion and migration (18). In PDAC, some investigators reported that EVencapsulated miRNAs, such as miR-196a, miR-1246, or miR-4644, could contribute to tumor development and play crucial roles in the diagnosis as tools of liquid biopsy (19)(20)(21).…”
Section: Introductionmentioning
confidence: 72%
“…We previously reported that EV-mediated transfer of lncRNAs or miRNAs can mediate the phenotypes of neighboring hepatocellular carcinoma (HCC), CCA, and PDAC cells (8,18,(24)(25)(26). Intercellular transfer of miR-30e by CCA cell-derived EVs could inhibit EMT signaling in recipient CCA cells (18). Also, long intergenic ncRNA regulator of reprogramming could be transferred by HCC cellderived EVs and suppress chemoresistance in recipient HCC cells (26).…”
Section: Mir-622 Transfer By Evs Can Inhibit Pdac Cell Invasion and Mmentioning
confidence: 99%
“…Several studies have shown that the impact of EVs on surrounding cells varies by EV content and is regulated by cell conditions (41,42). Regarding the effect of EVs derived from senescent cells on cancer cells, Takasugi et al (43) showed that EVs derived from senescent cells are absorbed by several breast cancer cell lines via EphA2, which resulted in SASP factor-like cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…When miR-30e containing exosomes were used to treat CCA cells, there was suppression in cell invasion and migration, along with EMT inhibition. 143 TRIM59 gene is a tumour promoting factor in breast cancer cells, which modulates the PDCD10 and results in the suppression of its associated signalling pathway, ROCK 1. 144 miR-148b-3p is poorly expressed in breast cancer tissues as studied by Yuan., et al Human umbilical cord mesenchymal stem cell (HUCMSC) derived exosomes containing miR-148b-3p, when co-cultured with MDA MB-231 cell lines, induced downregulation of TRIM 59 gene expression, thereby suppressing the progression of breast cancer and inhibiting EMT.…”
Section: Naturally Occurring Biomembranesmentioning
confidence: 99%